Non-structural Carbohydrate Metabolism in the Flesh of Stone Fruits of the Genus Prunus (Rosaceae) – A Review - Walker, Robert P.; Battistelli, Alberto; Bonghi, Claudio; Drincovich, María F.; Falchi, Rachele; Lara, María V.; Moscatello, Stefano; Vizzotto, Giannina; Famiani, Franco (Frontiers in Plant Science, 2020)
Non-structural carbohydrates are abundant constituents of the ripe flesh of all stone fruits. The bulk of their content comprises sucrose, glucose, fructose and sorbitol. However, the abundance of each of these carbohydrates in the flesh differs between species, and also with its stage of development. In this article the import, subcellular compartmentation, contents, metabolism and functions of non-structural carbohydrates in the flesh of commercially cultivated stone fruits of the family Rosaceae are reviewed.